Chuck. The complete fourth season [videorecording (DVD)] - Schwartz, Josh, 1976-; Fedak, Chris; Levi, Zachary, 1980-; Strahovski, Yvonne, 1982-; Gomez, Joshua, 1975-; McPartlin, Ryan, 1975-; Lawrence, Mark Christopher, 1964-; Sahay, Vik; Krinsky, Scott, 1968-; Ling, Julia, 1983-; Lancaster, Sarah, 1980-; Baldwin, Adam, 1962- (Warner Home Video, 2011)
Operation Wedded Bliss: will Chuck and Sarah finally become Mr. and Mrs. Superspy? Season Four's 24 laugh- and action-filled episodes include the duo's romance from proposal to planning to the big day. Yes, Chuck's in love, but he has more than romance (and the Intersect) on his mind. His mom comes in from the cold, escaping the evil control of an international arms dealer to become part of the Nerd Herder turned spy's life, and more.